Sosiologi Sejarah: Telaah Kritis Tentang Teori dan Sejarah Abad XX - Abd. Rahman . (ETNOHISTORI: Jurnal Ilmiah Kebudayaan dan Kesejarahan, 2015)
In the late twentieth century, many theorists seem to agree that a sociologymust be an historical sociology. Abrams went so far as to call historicalsociology ‘the essence of the discipline’, arguing that is ‘almost natural to themodern western mind’ to explain the contemporary world at least partly inhistorical terms What is historical sociology? Skocpol lists four characteristicsof historical studies: They ask question about social structures or processesunderstood to be concretely situated in time and space; They addressprocesses over time, and take temporal sequences seriously in accounting foroutcomes; They mostly attend to the interplay of meaningful action andstructural context, in order to make sense of the unfolding of unintended aswell as intended outcomes in individual lives and social transformations; They'highlight the particular and varying features of specific kinds of socialstructures and patterns of change'.